Artifacts in Electroencephalography: Clinical Cases and Electroencephalography Examples - (:unkn) unknown (TURKIYE KLINIKLERI, 2019)
In electroencephalography, electrical signals originating from extracerebral sources are called artifacts. The word artifact originates from the word artificial. Today, although the use of modern amplificators, artifacts are present almost in every electroencephalography. Artifacts can originate from a variety of sources. In clinic, artifacts are important in obscuring the normal electroencephalography recordings as well as being interpreted as pathologic activities. Recognizing artifacts in an electroencephalography recording is one of the basic principles of electroencephalography reading. The electroencephalography reader should always keep in mind that a suspicious wave form can be an artifact. Reporting artifacts as pathologic activities is one of the major causes in misinterpreting electroencephalographies as abnormal.
Keywords: Electroencephalography; artifacts